KEPENTINGAN SELANDIA BARU MELAKUKAN KERJASAMA PERDAGANGAN BEBAS DENGAN INDONESIA DALAM KERANGKA AANZFTA TAHUN 2012-2015 - Fajri, Desti Anandya; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
New Zealand is a small country, the same size with the Britania Raya or Japan, with a population of only four million people, this country including desolation. New Zealand diplomatic relations - Indonesia has been established since 1958. As the two democratic countries, Indonesia and New Zealand have the basis of the relationship established. This research aims to explain the ASEAN - Australia - New Zealand Free Trade Area (AANZFTA), explains the existence of economic and political interests of New Zealand against Indonesia and explained the New Zealand free trade cooperation with Indonesia in the framework of the AANZFTA Year 2012-2015.This research uses qualitative research methodology that is eksplanatif i.e. a research that tries to explain from some formulation of problems that the writer take. This research limits on : 1) the interests of the New Zealand free trade cooperation with Indonesia in the framework of the AANZFTA, 2) This Research focused on the year 2012-2015, where actually in that year Indonesia and New Zealand in the period of the implementation of the cooperation agreement AANZFTA.Based on the results of the research that has been carried out against this research, so it can be taken some conclusions, namely International Trade tax revenue from 2012-2014 export tax declined significantly, New Zealand is the main producer of products made from milk (dairy products) and flesh, timber and wood products, fish and other cereal products, machinery and agricultural products such as fruit and grain. New Zealand political influence for Indonesia because hdiplomatic ubungan Indonesia - New Zealand has been established since 1958.Keyword : Interests, New Zealand, Indonesia, Free Trade, AANZFTA, Years 2012-2015